Optimal design of laminated composite and nanocomposite structures using evolutionary optimization techniques: a survey - Moyo, Ranganai T.; Tabakov, Pavel Y. (Advances in Computing and Engineering, 2024)
The optimal design of laminated composite and nanocomposite (LCNC) structures stands at the forefront of materials engineering, offering the potential to revolutionize the development of advanced materials with superior mechanical, thermal, and electrical properties. By tailoring LCNC structures to meet specific performance requirements, optimizing material usage, and exploring innovative design approaches, engineers can create lighter, more efficient, and environmentally friendly structures that excel in diverse applications. Many industries such as automotive, aerospace, and construction are already using composite and nanocomposite materials to develop high-strength and lightweight structures. Thus, this survey delves into evolutionary optimization techniques as powerful tools for achieving optimal configurations in LCNC structures, highlighting the importance of selecting the appropriate technique for a given optimization problem. A strict selection method was employed to come up with this review paper, and only reputable literary sources were used. Common design optimization problems such as buckling load, vibration, and weight & cost minimization are covered. Received: 16 July 2024 Accepted: 24 August 2024 Published: 05 September 2024